Improving sustainable crop protection using population genetics concepts - Méline Saubin; Clémentine Louet; Lydia Bousset; Frédéric Fabre; Pascal Frey; Isabelle Fudal; Frédéric Grognard; Frédéric Hamelin; Ludovic Mailleret; Solenn Stoeckel; Suzanne Touzeau; Benjamin Petre; et al. (Molecular Ecology, 2023)
Growing genetically resistant plants allows pathogen populations to be controlled and reduces the use of pesticides. However, pathogens can quickly overcome such resistance. In this context, how can we achieve sustainable crop protection? This crucial question has remained largely unanswered despite decades of intense debate and research effort. In this study, we used a bibliographic analysis to show that the research field of resistance durability has evolved into three subfields: (1) “plant breeding” (generating new genetic material), (2) “molecular interactions” (exploring the molecular dialogue governing plant–pathogen interactions) and (3) “epidemiology and evolution” (explaining and forecasting of pathogen population dynamics resulting from selection pressure[s] exerted by resistant plants). We argue that this triple split of the field impedes integrated research progress and ultimately compromises the sustainable management of genetic resistance. After identifying a gap among the three subfields, we argue that the theoretical framework of population genetics could bridge this gap. Indeed, population genetics formally explains the evolution of all heritable traits, and allows genetic changes to be tracked along with variation in population dynamics. This provides an integrated view of pathogen adaptation, in particular via evolutionary–epidemiological feedbacks. In this Opinion Note, we detail examples illustrating how such a framework can better inform best practices for developing and managing genetically resistant cultivars.

Soil and plant health in relation to dynamic sustainment of Eh and pH homeostasis: A review - Olivier Husson; Jean-Pierre Sarthou; Lydia Bousset; Alain Ratnadass; Hans-Peter Schmidt; John Kempf; Benoit Husson; Sophie Tingry; Jean-Noël Aubertot; Jean-Philippe Deguine; François-Régis Goebel; Jay Ram Lamichhane (Plant and Soil, 2021)

An easy, rapid and accurate method to quantify plant disease severity: application to phoma stem canker leaf spots - Lydia Bousset; Stéphane Jumel; Hervé Picault; Claude Domin; Lionel Lebreton; Arnaud Ribulé; Régine Delourme (European Journal of Plant Pathology, 2016)

Disentangling the genetic origins of a plant pathogen during disease spread using an original molecular epidemiology approach - CONSTANCE XHAARD; BENOÎT BARRÈS; AXELLE ANDRIEUX; LYDIA BOUSSET; FABIEN HALKETT; PASCAL FREY (Molecular Ecology, 2012)
The advent of molecular epidemiology has greatly improved our ability to identify the population sources and track the pathogen movement. Yet the wide spatial and temporal scales usually considered are useful only to infer historical migration pathways. In this study, Bayesian genetic assignments and a landscape epidemiology approach were combined to unravel genetic origin and annual spread during a single epidemic of a plant pathogen: the poplar rust fungus Melampsora larici‐populina . The study focused on a particular area—the Durance River valley—which enabled inoculum sources to be identified and channelled spread of the epidemic along a one‐dimensional corridor. Spatio‐temporal monitoring of disease showed that the epidemic began in the upstream part of the valley and spread out downstream. Using genetic assignment tests, individuals collected at the end of the epidemic were sorted into two genetic groups; very few hybrids were detected, although individuals from both groups coexisted locally downstream in the valley. The epidemic originated from two genetically distinct inoculum sources. Individuals of each group then dispersed southwards along the Durance River and became mixed in poplar riparian stands. These two genetic groups were found previously at a wider spatial scale and proved to result from distinct evolutionary histories on either wild or cultivated poplars. This study showed that the two groups can mix during an epidemic but do not hybridize because they then reproduce asexually. In general, the methods employed here could be useful for elucidating the genetic origin and retracing the colonization history and migration pathways of recent epidemics.

Barley Powdery Mildew Populations on Volunteers and Changes in Pathotype Frequencies During Summer on Artificially Inoculated Field Plots - Lydia Bousset; Claude de Vallavieille-Pope (European Journal of Plant Pathology, 2003)

Effect of Sexual Recombination on Pathotype Frequencies in Barley Powdery Mildew Populations of Artificially Inoculated Field Plots - Lydia Bousset; Claude de Vallavieille-Pope (European Journal of Plant Pathology, 2003)